Chest pain in children with familial Mediterranean fever - Sunar-Yayla, Emine Nur; Şenol, Pelin Esmeray; Yıldırım, Deniz Gezgin; Söylemezoğlu, Oğuz (The Turkish Journal of Pediatrics, 2023)
Background. Familial Mediterranean fever (FMF) is the most common and autosomal recessive inherited autoinflammatory disease. The most common signs and symptoms are fever, abdominal pain, chest pain, and arthritis. The aim of this study was to describe the clinical, laboratory and genetic differences between pediatric FMF patients with and without chest pain. Methods. Between January 2006 and January 2022, 1134 patients with FMF were analyzed retrospectively. Patients were divided into two groups including those with and without recurrent chest pain. These groups were compared in demographic, clinical, treatment, and MEFV gene analyses. Results. A hundred and sixty-two (14.3%) patients had recurrent chest pain. In patients with recurrent chest pain, the age of onset of symptoms was younger (p=0.003), and the family history of FMF was higher (p=0.002). Patients with chest pain had a higher annual attack frequency (p < 0.001), a longer attack duration (p < 0.001), and higher Pras disease activity scores (p < 0.001). The colchicine dose used in the treatment was higher in FMF patients with chest pain (p=0.005), and anti-IL-1treatment was higher (p < 0.001). M694V homozygous mutation was found more frequently (p=0.001), whereas M694V/V726A mutation was found less frequently in patients with recurrent chest pain (p=0.017). Conclusions. Patients with recurrent chest pain seem to have early onset symptoms, often are more likely to have family history, and have a higher disease severity. In addition, the presence of homozygous M694V mutation is more common in patients with chest pain.
Keywords: chest pain; familial Mediterranean fever; pleurisy; pyrin